2017
DOI: 10.1016/j.aott.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the mobility of medial longitudinal arch and postural control

Abstract: ObjectiveThe aim of this study was to analyze the relationship between the medial longitudinal arch mobility and static and dynamic balance.MethodsA total of 50 subjects (25 female, and 25 male; Mean age: 22.2 ± 1.3 years; BMI: 22.8 ± 3.8 kg/m2) were included in this study. The relative arch deformity (RAD) was calculated with both 10% and 90% weight bearing (WB). Static balance was evaluated with Single Leg Stance Test and dynamic balance with TechnoBody PK 200WL computerized balance device. Subjects were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
1
15
1
1
Order By: Relevance
“…Although previous studies reported changes in arch function leading to some balancing improvement (Birinci & Demirbas, 2017), no significant change was observed in mSEBT in the SFE group in this study. A significant improvement was observed in the non-SFE group, possibly because the training with the unstable plate improved the nerve-muscle coordination and postural control in the one-leg standing position.…”
Section: Discussioncontrasting
confidence: 94%
“…Although previous studies reported changes in arch function leading to some balancing improvement (Birinci & Demirbas, 2017), no significant change was observed in mSEBT in the SFE group in this study. A significant improvement was observed in the non-SFE group, possibly because the training with the unstable plate improved the nerve-muscle coordination and postural control in the one-leg standing position.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast, toe flexor strength, which is caused by the action of the flexor digitorum longus, flexor hallucis longus, and flexor digitorum brevis muscles, is considered to be an important factor involved in walking and standing ability, risk of falling, and balance stability 12 , 13 , 14 , 15 , 16 ) . Moreover, toe flexor strength has been reported to be associated with the foot arch, and it is recognized that short foot exercises for intrinsic muscles of the foot to improve the MLA in flatfoot result in improved results in the arch height index 17 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This correlation was apparent in the static conditions, whereas in the dynamic ones such correlations were not noted. Birinci et al [26] asserted that the reduced mobility of the foot arch was bound to affect overall postural control and COP sways. These changes induce a different arrangement of the higher located segments of the body, as they simply have to adapt accordingly.…”
Section: Discussionmentioning
confidence: 99%